How do you verify that the given trigonometric equation is correct and satisfy the condition, the given function is \[\left( {\cos (x)} \right)\left( {\cos (x)} \right) = 1 - {\sin ^2}x\]?
Answer
Verified
442.5k+ views
Hint: To prove a trigonometric function either we can use direct properties available for the function to achieve our result or you can satisfy the equation by assuming any angle and get that left the hand side of the equation is equal to the right hand side, both ways are correct, accurate and will give the result.
Formulae Used:
\[ \Rightarrow {\sin ^2}x + {\cos ^2}x = 1\]
Complete step by step solution:
The given question is \[\left( {\cos (x)} \right)\left( {\cos (x)} \right) = 1
- {\sin ^2}x\]
Here we will solve this question first by using the trigonometric property that is:
\[ \Rightarrow {\sin ^2}x + {\cos ^2}x = 1\]
By rearranging the splitting the above property we get:
\[
\Rightarrow {\sin ^2}x + {\cos ^2}x = 1 \\
\Rightarrow {\cos ^2}x = 1 - {\sin ^2}x \\
\]
Here we obtain our result.
Now lets satisfy the given equation at zero degree, on solving we get:
\[
\Rightarrow \left( {\cos (x)} \right)\left( {\cos (x)} \right) = 1 - {\sin ^2}x \\
\Rightarrow \cos (0) = 1,\,and\,\sin (0) = 0 \\\]
Putting the values, we get:
\[\Rightarrow \cos (0)\cos (0) = 1 - {\sin ^2}(0) \\
\Rightarrow 1 \times 1 = 1 - {\left( 0 \right)^2} \\
\Rightarrow 1 = 1 - 0 \\
\Rightarrow 1 = 1 \\
\]
Here also we obtain that the left hand side and right hand side of the given equation gives the same value on the assumed angle, and since it's already a trigonometric property hence will satisfy for every angle.
Additional Information: Here you can solve after transforming every term into a single function then you will get that the given function of “sin” and “cos” will become one and one minus one will give you zero which is present on the right side of the equation.
Note: To prove any trigonometric equation you can also simplify the equation and since every trigonometric function is inter relatable and accordingly you can solve for it, with this method you can convert every given function into one trigonometric identity and then you can prove for left hand side of equation equals to right hand side.
Formulae Used:
\[ \Rightarrow {\sin ^2}x + {\cos ^2}x = 1\]
Complete step by step solution:
The given question is \[\left( {\cos (x)} \right)\left( {\cos (x)} \right) = 1
- {\sin ^2}x\]
Here we will solve this question first by using the trigonometric property that is:
\[ \Rightarrow {\sin ^2}x + {\cos ^2}x = 1\]
By rearranging the splitting the above property we get:
\[
\Rightarrow {\sin ^2}x + {\cos ^2}x = 1 \\
\Rightarrow {\cos ^2}x = 1 - {\sin ^2}x \\
\]
Here we obtain our result.
Now lets satisfy the given equation at zero degree, on solving we get:
\[
\Rightarrow \left( {\cos (x)} \right)\left( {\cos (x)} \right) = 1 - {\sin ^2}x \\
\Rightarrow \cos (0) = 1,\,and\,\sin (0) = 0 \\\]
Putting the values, we get:
\[\Rightarrow \cos (0)\cos (0) = 1 - {\sin ^2}(0) \\
\Rightarrow 1 \times 1 = 1 - {\left( 0 \right)^2} \\
\Rightarrow 1 = 1 - 0 \\
\Rightarrow 1 = 1 \\
\]
Here also we obtain that the left hand side and right hand side of the given equation gives the same value on the assumed angle, and since it's already a trigonometric property hence will satisfy for every angle.
Additional Information: Here you can solve after transforming every term into a single function then you will get that the given function of “sin” and “cos” will become one and one minus one will give you zero which is present on the right side of the equation.
Note: To prove any trigonometric equation you can also simplify the equation and since every trigonometric function is inter relatable and accordingly you can solve for it, with this method you can convert every given function into one trigonometric identity and then you can prove for left hand side of equation equals to right hand side.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE